Analisis Pendapatan dan Saluran Pemasaran Usahatani Jamur Tiram (Pleurotus Ostreatus) di Barokah Jaya Kelurahan Mangli Kecamatan Kaliwates Kabupaten Jember - Rusdiana Sholehah, Dewi; Wahyu Pudjiastutik, Endang (KUBIS, 2022)
Mushrooms are one type of horticultural products that can be developed and directed to be able to improve the nutritional state of society. Oyster mushrooms are a safe food to consume due to the relatively little use of pesticides and chemicals. Efficient marketing channels are influenced by the relevant marketing institutions in them. The purpose of this study is (1) Analyzing the income efficiency of white oyster mushroom farming in Barokah Jaya, (2) Knowing the marketing chain of white oyster mushrooms in Barokah Jaya and (3) Analyzing the marketing efficiency of oyster mushrooms in Barokah Jaya. The sampling method used in this study is purposive sampling technique that is sampling with the aim of businesses. Based on the results of the analysis of the efficiency of oyster mushroom farming revenue from 2015 to 2019 R/C ratio is greater than one. The highest R/C ratio in 2018 was R/C ratio over Total Cost of 9.4 and R/C cash cost ratio of 12.5. In 2015, 2016 and 2019 with the lowest R/C ratio of R/C ratio over Total Cost of 8.54 and R/C cash cost ratio of 10.9. Barokah Jaya has two marketing channels, farmer's share channel pattern one in 2015, 2016 and 2019 by 70.00 percent in 2017 by 75.00 percent and in 2018 by 71.05 percent. Farmer's share of channel two patterns in 2015, 2016 and 2019 was 77.8 percent, 2017 was 80.00 percent and 2018 was 79.4 percent. Of the two marketing channels above the most profitable are in the second marketing channel pattern.